2011
DOI: 10.1136/tc.2011.044040
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation medications and cigarettes in Guatemala pharmacies

Abstract: Most pharmacies in Guatemala do not stock cessation medications or cigarettes. Cigarette advertising was more prevalent than advertising for cessation medications. FCTC provisions have not been implemented in Guatemala pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Little research examined any form of smokeless tobacco, cigars, cigarillos or other tobacco products. For example, the only examination of e-cigarette availability we identified was conducted in Guatemalan pharmacies 81. In an effort to document the availability and variety of culturally-specific tobacco products, Longman et al audited stores in South Asian immigrant communities in England, identifying 98 different smokeless tobacco products,59 and Schensul et al identified 68 smokeless tobacco products in low-income areas of Mumbai 72…”
Section: Resultsmentioning
confidence: 99%
“…Little research examined any form of smokeless tobacco, cigars, cigarillos or other tobacco products. For example, the only examination of e-cigarette availability we identified was conducted in Guatemalan pharmacies 81. In an effort to document the availability and variety of culturally-specific tobacco products, Longman et al audited stores in South Asian immigrant communities in England, identifying 98 different smokeless tobacco products,59 and Schensul et al identified 68 smokeless tobacco products in low-income areas of Mumbai 72…”
Section: Resultsmentioning
confidence: 99%
“…(Saccone, Emery, Sofer, et al, n.d.; Kaplan, Bangdiwala, Barnhart, et al, 2014). Research funded by international agencies has documented determinants of smoking and smoking cessation, including the frequency of smoking, the availability of single cigarettes, (Thrasher, Villalobos, Barnoya, Sansores, & O’Connor, 2011) the lack of cessation medications, (de Ojeda, Barnoya, & Thrasher, 2013; Viteri, Barnoya, Hudmon, & Solorzano, 2012) and the impact of tax increases. (Saenz de Miera Juarez, Thrasher, Reynales Shigematsu, Hernandez Avila, & Chaloupka, 2014).…”
Section: Populations and Settingsmentioning
confidence: 99%
“…3 Data from developing countries are rare, but one recent study has suggested that just 5.7% of pharmacies in Guatemala sell tobacco products. 4 Concern over pharmacy sale of tobacco in the USA has led to the introduction of new local tobacco control policies. In 2008, San Francisco became the first American city to prohibit pharmacies from selling tobacco products.…”
Section: Introductionmentioning
confidence: 99%